The contribution of individual psychological resilience in determining the professional quality of life of Australian nurses - Hegney, Desley G.; Rees, Clare S.; Eley, Robert; Osseiran-Moisson, Rebecca; Francis, Karen (Frontiers in Psychology, 2015)
Research Topic: The aim of this study was to determine the relative contribution of trait negative affect and individual psychological resilience in explaining the professional quality of life of nurses. In particular, we sought to test whether resilience would mediate the relationship between trait negative affect and compassion satisfaction. Methods: One thousand, seven hundred and forty-three Australian nurses from the public, private and aged care sectors completed an online Qaltrics survey. The survey collected demographic data as well as measures of depression, anxiety and stress, trait negative affect, resilience and professional quality of life. Results: Significant positive relationships were observed between anxiety, depression and stress, trait negative affectivity, burnout and secondary traumatic stress (compassion fatigue). Significant negative relationships were observed between each of the aforementioned variables and resilience and compassion satisfaction. Results of mediated regression analysis indicated that resilience partially mediates the relationship between trait negative affect and compassion satisfaction. Conclusions: Results confirm the importance of both trait negative affect and resilience in explaining positive aspects of professional quality of life. Importantly, resilience was confirmed as a key variable impacting levels of compassion satisfaction and thus a potentially important variable to target in interventions aimed at improving nurse’s professional quality of life.